Phase transfer catalysis by tetraethylammonium bromide: Oxidation of primary and secondary alcohols using potassium superoxide in aprotic medium - Shukla A.K.; Singh K.N. (My University, 2025)
Tetraethylammonium superoxide, generated in situ by the phase transfer reaction of potassium superoxide and tetraethylammonium bromide, readily oxidises the primary and secondary alcohols in dry dimethylibrmamide at room temperature. As a result, primary alcohols are transformed into their corresponding acids whereas secondary alcohols are converted to ketones in fairly good yields. The report demonstrates the applicability of tetraethylammonium bromide as phase transfer catalyst for efficient superoxide studies.